Economic Evidence on Cost Sharing and Alternative Insurance Designs to Address Moral and Behavioral Hazards in High-Income Health Care Systems: A Systematic Review - Marlon Graf; James R. Baumgardner; Ulrich Neumann; Iris P. Brewer; Jacquelyn W. Chou; A. Mark Fendrick (Journal of Market Access & Health Policy)
In health insurance, “moral hazard” describes the concept that coverage without an out-of-pocket cost to consumers could result in health care utilization beyond economically efficient levels. In response, payers in the United States (US) have designed pharmaceutical benefit plans with significant cost exposure (e.g., co-pays, co-insurance, or deductibles). While substantial evidence links patient cost exposure to reduced drug spending, it remains unclear to what degree this translates into greater efficiency or an indiscriminate drop in overall consumption also reducing needed utilization. We conducted a systematic literature review to understand whether commonly implemented utilization management (UM) strategies and insurance designs with a behavioral or value-based (BID/VBID) component have been explored as tools to mitigate moral hazard and to assess how cost-sharing policies and innovative insurance designs impact consumer spending. Eligible studies compared conventional cost-exposure policies to BID/VBID, including tiered cost-sharing and other UM strategies. We found that broad implementation of patient cost exposure is not well supported by empirical evidence assessing efficiency—defined as the use of clinically appropriate services with value at or above the marginal cost of health care utilization in the contemporary US setting. As a result, payers and policy makers alike ought to explore insurance alternatives that more closely align health care consumption incentives to value of care.